Stability Analysis of Nonlinear Oscillations for AC-Fed Electric Arc Furnaces in Context of Bifurcation Dynamics - Varan, M.; Uyaroğlu, Y. (Elektronika ir Elektrotechnika, 2013)
Bifurcation theory has been widely used to investigate dynamic behaviours of nonlinear components, and to make analytical answers on formation of synchronous resonanace , chaotic oscillations and ferroresonance oscillations phenomenon in electrical engineering. Bifurcation theory is also applied to perform stability analysis in nonlinear systems. This study aims to identify formations of nonlinear oscillations produced by AC-Fed Electric Arc Furnaces, in regard with bifurcation dynamics on system. During study, possible roles of small parameter changes of sample arc furnace system around bifurcation points has been traced over time series analysis, phase plane analysis and bifurcation diagrams. A wide collection of useful dynamic analysis procedures for the exploration of studied arc furnace dynamics have been handled through the AUTO open-source algorithms. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.1556